Co-application of organic amendments and inorganic P increase maize growth and soil carbon, phosphorus availability in calcareous soil - Khan, Khuram Shehzad; Ali, Muhammad Moaaz; Naveed, Muhammad; Rehmani, Muhammad Ishaq Asif; Shafique, Muhammad Waleed; Ali, Hayssam M.; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; Feng, Gu (Frontiers in Environmental Science, 2022)
Phosphorus (P) constraint can be alleviated by increasing C inputs, which can help to improve crop production and P fertilizer use efficiency. However, the effects of different manures on soil microbial biomass P (MBP) and P fractions as well as C fractions in calcareous soils remain poorly understood. Soil MBP pool involves the P mineralization and immobilization processes, potentially changing P fractions and P availability. Therefore, the effects of different manures on soil microbial biomass (MBP, MBC) pool, P, and C fractions and crop P utilization were evaluated in greenhouse experiments with maize plantation. Treatments included no manure (control), poultry manure (PM), cow manure (CM), goat manure (GM), mixed manure (MM), and three inorganic P (Pi) rates; P0: 0 mg kg-1, P50: 50 mg kg-1, and P100: P100 mg kg-1 (P2O5). For plant growth comparison, crop physiological growth indices, shoot P contents and total P uptake were increased by PM and P100 as compared to other treatments. The PM with P100 significantly increased the plant growth by inducing P uptake of ∼18% compared with control. The results exhibited that Pi (P100) combined with manure (PM) significantly (p < 0.05) increased the soil physicochemical properties, that is, 683.76 mg kg-1 total P, 21.5 mg kg-1 Olsen P, 4.26 g kg-1 SOC, 2.41 g kg-1 POC, as well as microbial biomass C and P increased by 152.84 mg kg-1 and 36.83 mg kg-1, respectively. Consequently, we concluded that PM with Pi (P100) application builds up soil microbial biomass, which is more beneficial for promoting P utilization for maize.